Analysis of Voltage Difference Characteristics of Albumin Membranes and Vitelin Membranes of Chicken Eggs through Diazinon Effects - Wira Dian Jauharah; Didik Rahadi Santoso; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2017)
Cells are the most important structural and functional part of any organism. Cells are protected by cell membranes that envelop cells, and separate cells with their environment. The effectiveness of the work of a cell membrane can be disrupted for various reasons, one of which is pesticide contamination. Pesticides in cells can damage cell metabolism or cell membrane permeability. Therefore, this study aims to determine how big the effect of diazinon insecticides on the characteristics of different potential membrane vitelin and membrane albumin chicken egg cells. Measurements were made using the microelectrode connected with the picoscope 5000 series, then the data appears displayed through the PC. The results of membrane potential measurements showed that the greater the concentration of insecticide given, the potential value of chicken egg membrane increased. Potential Differential Values Membrane of eggs with different concentrations ranged in -145 mV - 249 mV on vitelin membrane, and -142,5 mV - 242,5 mV on albumin membrane